Fruit flies on the front line: the translational impact of Drosophila - Norbert Perrimon; Nancy M. Bonini; Paraminder Dhillon (The Company of Biologists, 2016)
Drosophila melanogaster has been adopted as one of the most-used model systems since it was first introduced by Thomas Morgan for the study of heredity in the early 20th century. Its experimental tractability and similarity of its biological pathways to those of humans have placed the model at the forefront of research into human development and disease. With the ongoing accumulation of genetic tools and assays, the fly community has at its fingertips the resources to generate diverse Drosophila disease models for the study of genes and pathways involved in a wide range of disorders. In recent years, the fly has also been used successfully for drug screening. In this Editorial, we introduce a Special Collection of reviews, interviews and original research articles that highlight some of the many ways that Drosophila has made, and continues to make, an impact on basic biological insights and translational science.